The Role and Future Development of Meals-on-Wheels Services for Older People in Ireland - Timonen, Virpi (National Council on Ageing and Older People, 2008)
In recent years, the National Council on Ageing and Older People (NCAOP) has noted the increased recognition of the importance of the meals-on-wheels services in improving older people?s nutritional status, health and quality of life. In addition, there has been an increased awareness of the service as a vital source of social contact and connectivity for many older people who are vulnerable to social exclusion and social isolation: The meals-on-wheels service provides regular meals and essential social contact for many older people. In this way the service will contribute to older people remaining at home and in better health. Though the meals-on-wheels service has been in existence for some decades, the Council noted a dearth of information relating to it. As a result, the NCAOP commissioned this study in order to provide a comprehensive picture of the service. The Council now recommends that its findings be used by all stakeholders to inform future service developments.
PUBLISHED
Dublin
Keywords: meals-on-wheels; nutrition; older people; community care